WOMEN'S CONCEPTION REGARDING PAPANICOLAOU TEST IN MIRANDÓPOLIS-SÃO PAULO - Gean Domingos da Silva Souza; Rafaela Azevedo Abrantes de Oliveira; Annies Stevanin; Mariana Ferreira Sousa; Elton Carlos de Almeida (Universidade Federal de Santa Maria, 2013)
http://dx.doi.org/10.5902/217976929647 Aim: To verify the knowledge of women Mirandópolis- São Paulo about on the Pap smear. Method: Field research exploratory descriptive quantitative approach, performed in the city of Mirandópolis - São Paulo, with a sample of a hundred women, who answered a self-administered questionnaire. Data were analyzed with SPSS software, and arranged in percentage. Results: The data showed that 83% of women have performed the Pap smear, 42% of them perform the test once a year, with a loss of periodicity recommended by the Ministry of health. The embarrassment and lack of time presented as the main barrier for not performing the Pap smear. Conclusion: CCU screening should be focused on knowledge, and the reduction of the factors contributing to not realization of the pap smear, which comes from a relationship of trust and empathy among users and health professionals.